Surgical Management of Comminuted Distal Femoral Fracture Using Intramedullary Pin in a Cat - Putri, Cindy Ercha Aulia; Rahmatullah, Aldin Akbar; Afandi, Mohammad Auzaie; Halim, Muhammad Al-Syafiq bin Abdul (Media Kedokteran Hewan, 2025)
A 3-year-old male domestic short-haired cat, weighing 3.8 kg, was presented with lameness, swelling in the left hind limb groin area, and pain upon palpation. Radiographic examination confirmed a comminuted fracture in the diaphysis of the left femur. This case report aims to document the diagnostic approach and surgical management using an intramedullary pin technique. Surgical intervention was performed to restore the anatomical alignment of the fracture fragments. The procedure involved open reduction and internal fixation using an intramedullary pin. Post-operative medication included tramadol (1 mg/kg BW) for analgesia, ceftriaxone (25 mg/kg BW) as antibiotic therapy, and dexamethasone (2 mg/kg BW) for anti-inflammatory effects. Femoral fractures account for 20-26% of fractures in cats, with various treatment options available including pins and wires, Rush pins, threaded intramedullary pins, interlocking pins, clamp rod internal fixators, and plate-rod systems. The intramedullary pin technique was selected for this case due to its suitability for comminuted diaphyseal fractures. This case highlights the efficacy of intramedullary pin fixation as a viable treatment option for comminuted femoral fractures in cats when appropriate surgical technique and post-operative care are implemented.